MECHANISMS FOR DEVELOPING INDEPENDENT THINKING IN READING AND MOTHER LANGUAGE TEXTBOOKS (Universal International Scientific Journal, 2026)
This article interprets reading and mother tongue textbooks in primary education asimportant didactic tools for shaping students’ thinking. The system of texts, questions, and tasks in thetextbooks is scientifically described as a step-by-step process that leads students from simple readingto deep comprehension, from comprehension to analysis, and from analysis to independent and criticalthinking. Exercises such as picture-based storytelling, creating sentences and proverbs from givenwords, and analyzing problem situations are evaluated as mechanisms for enhancing cognitiveactivity. Based on the experience of integrated textbooks, effective methodological approaches fordeveloping independent thinking are proposed.
Keywords: primary education; reading literacy; mother tongue textbooks